Fragments d'une révolution - Anonymous (France; Iran, 2010)
"Fragments of a Revolution" follows numerous demonstrations which took place in Iran as early as June 2009 at the time of the presidential elections. The director, who is in Paris, lives the events through the amateur videos she collects and archives relentlessly.
Anonymous directors
Verzio Film Festival Submission
Keywords: Documentary films